Complex estimation of invasive fitophages pestfulness of different tropho-ecological groups damaging decorative woody plants under the conditions in Grodno Poneman region - Hliakouskaya, Katsiaryna I. (Experimental Biology and Biotechnology, 2019)
The calculation of the physiological and general damage indices for 38 species of invasive phytophagous insects affecting the green plantations of the Grodno Ponemanjan green plantation has been done. The maximum value of the index of total damage (126 points) marked for hopping aphid (Tinocallis saltans (Nevsky, 1929)), white-gallic gall bladder Obolodiplosis robiniae (Haldeman, 1847) (222.75 points) which damaging the common rhinitis (Robinia pseudoacacia L.) and chestnut miner moths (Cameraria ohridella Deschka & Dimic, 1986) – one of the most widespread pests of green plantations of Belarus and continental Europe.
Keywords: pests; alien species; sucking and gall-forming insects and mites; phyllophagous; Belarus